Analysis of Safety Management in Precast Construction Projects - et al., Rohan Chopade (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Construction is the second-largest economic activity in India, next to agriculture. Construction workers constitute 7 to 8% of the world's labor force and this figure may be as high as 15 to 20% in some countries. Construction is one of the important economic activities in India. The construction industry offers employment opportunities to all people from highly skilled to unskilled labourers. At a construction site, several people work at the same time at the same different levels. Workers, machines, overhead cranes, all should have to work in a congested area. The work should be carried out at a tremendous speed. Thus, construction work is hazardous by its nature itself. This study will try to put safety management in construction projects as one of the important elements to project performance and success. The study will also emphasise the awareness and importance of safety management in a construction project. Injuries and fatalities resulted in accidents in the construction industry.